Connexin 43 Communication Channels in Follicular Dendritic Cell Development and in Follicular Lymphomas. (2nd March 2015) - Rajnai, Hajnalka; Teleki, Ivett; Kiszner, Gergo; Meggyesházi, Nora; Balla, Peter; Vancsik, Tamas; Muzes, Gyorgyi; Csomor, Judit; Matolcsy, Andras; Krenacs, Tibor
Abstract : Follicular dendritic cells (FDC) show homo- and heterocellular metabolic coupling through connexin 43 (Cx43) gap junctions and support B cell selection and maturation in germinal centers. In follicular lymphomas B cells escape apoptosis while FDC develop abnormally. Here we tested Cx43 channels in reactive FDC development and follicular lymphomas. In culture, the treatment of FDC-B cell clusters (resembling to " ex vivo " germinal centers) with Gap27 peptide, mimicking the 2nd extracellular loop of Cx43 protein, significantly impaired FDC-B cell cluster formation and cell survival. In untreated cultures of intact clusters, cell proliferation showed a moderate reduction. In tissues, Cx43 protein levels run parallel with the density of FDC both in reactive germinal centers and in malformed follicles of follicular lymphomas and showed strong upregulation in newly generated and/or degrading bi-/multinuclear FDC of rudimentary processes. However, the inverse correlation between Cx43 expression and B cell proliferation seen in reactive germinal centers was not detected in follicular lymphomas. Furthermore, Cx43 levels were not associated with either lymphoma grade or bone marrow involvement. Our results suggest that Cx43 channels are critical in FDC and " ex vivo " germinal center development and in the persistence of FDC in follicular lymphomas but do not affect tumor progression.